Hypoplastic left heart syndrome (HLHS): structural changes of the heart and the basis of morphogenesis - Kucherenko , Anastasiia; Savchuk , Tetiana (The Ukrainian Scientific Medical Youth Journal, 2024)
hypoplastic left heart syndrome is a complex congenital heart defect caused by a disorder of embryogenesis with the formation of mitral and aortic valve defects (atresia and/or stenosis) and hypoplasia of the left ventricle. The purpose of the work was to carry out a review and analysis of the scientific literature on the etiology, pathogenesis, morphogenesis, classifications, embryogenesis, existing methods of treatment of the defect. The analyzed data from Ukrainian and foreign literature were published in PubMed in the period 2014-2023. The results of the review indicate a 100% combination of hypoplasia of the left ventricle with defects of the aortic and mitral valves. In addition, the type of structure of the hypoplastic left ventricle depended on the combination of valvular defects (atresia or stenosis). There is no generally accepted classification of the syndrome in the literature. Five pathomorphological types of the left ventricle are described, depending on the shape of the cavity, the structure of the wall, the presence or absence of fibroelastosis: type I – slit-like hypoplastic (18.2%), with maximum hypoplasia of the left ventricle and the absence of endocardial fibroelastosis, which was always combined with arterial atresia and mitral valve. Type II – slit-like hypertrophic (19.2%); was characterized by the least hypoplasia of the left ventricle and correct architecture of myocardial fibers, absence of fibroelastosis; met with stenosis of both valves. The formation of the pathomorphological type with fibroelastosis of the endocardium depended on the diameter of the opening of the mitral valve, with the largest opening, type III - cylindrical (42.4%) was formed. Type IV (lacunar; the cavity is represented by numerous lacunae (6.1%)), was accompanied by myocardial dysplasia, resembling a non-compact myocardium; was formed at the smallest mitral opening, and type V – lacunar-cylindrical (14.1%), a cavity in the form of trabeculae and lacunae with expansion in the basal parts of the heart. In types with fibroelastosis, the aortic valve was always atresed. Conclusions: hypoplastic left heart syndrome is a complex congenital heart defect with 100% mortality without surgical treatment. The success of the treatment depended on the preliminary examination of the patient's heart, namely the establishment of the pathomorphological type of the left ventricle, changes in which determined the choice of treatment tactics. The Norwood procedure, the essence of which was to exclude the left ventricle from the blood flow and ensure blood circulation by the only right ventricle, is advisable to be performed on hearts with maximally hypoplastic left ventricles, which reduced the load on the right ventricle. The question of the implementation of fetal surgery for aortic valvuloplasty in the least hypoplastic types of structure with a normal structure of the left ventricular myocardium, which is associated with certain risks for the mother and the fetus, remains open. When types of left ventricle with fibroelastosis and myocardial dysplasia are detected prenatally, it is possible to recommend termination of pregnancy to the parents due to their unfavorable prognosis for any type of surgical correction.